CSR and financial performance: The role of CSR awareness in the restaurant industry. (August 2016) - Rhou, Yinyoung; Singal, Manisha; Koh, Yoon
Abstract: Initiatives for corporate social responsibility (CSR) often have served business as a source of competitive advantage. However, despite firms' attempts to capitalize on their CSR efforts, stakeholders' low awareness of these initiatives makes it difficult to realize the full value of the strategic CSR. In this study, we propose and test in the context of the restaurant industry whether CSR awareness, measured by CSR media coverage, moderates the relationship between the social and financial performance. Our results support the notion that stakeholders' CSR awareness affects the manner in which CSR initiatives can result in financial gain. Our research has implications both for firms' investment policies in social initiatives and for highlighting the importance of communicating CSR initiatives to relevant stakeholders.